If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+7=4-3(x+2)
We simplify the equation to the form, which is simple to understand
6x+7=4-3(x+2)
Reorder the terms in parentheses
6x+7=4+(-3x-6)
Remove unnecessary parentheses
+6x+7=+4-3x-6
We move all terms containing x to the left and all other terms to the right.
+6x+3x=+4-6-7
We simplify left and right side of the equation.
+9x=-9
We divide both sides of the equation by 9 to get x.
x=-1
| -8=-5(w+5) | | 2(x-6)+3=-3(4-x) | | 6x-12y=72 | | y=-7+5y | | 6x-16-3x=5x-9 | | 2-b+7b-2= | | 8.9y-7.35=12.4y | | 3-6x=-2x-37 | | 6+.10x=0.15x+8 | | -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= | | -6x-76=98-12x | | -1+6x=3x-19 | | (27p^6)^(5/3) | | -6-k+2-5k= | | 8x-2(x-8)=6(x+1)+7 | | 5-10t=-25 | | 40=5x+2(-x+2) | | x^2-23x=3 |